Answer:
I would think Jessica
Step-by-step explanation:
V36-->6 bc 6*6=36
Again, im pretty sure this is your answer not completely positive
The answer is 4 like i sed last time stop making conversation nd get to work
Answer:
B. -7
Step-by-step explanation:
f(x) = 4x + 5
To find the value of f(-3), replace all the x's in f(x) with -3.
f(x) = 4x + 5
f(-3) = 4(-3) + 5
f(-3) = -12 + 5
f(-3) = -7.
This makes your answer B, -7.
Answer:
I don't know if this helps, just a picture not a link
Answer:
p = -2 ±sqrt( 5)
Step-by-step explanation:
p^2 + 4p = 1
Take the coefficient of p
4
Divide by 2
4/2 =2
Square it
2^2 = 4
Add it to each side
p^2 + 4p+4 = 1+4
(p+2) ^2 = 5
Take the square root of each side
sqrt((p+2) ^2) =±sqrt( 5)
p+2 = ±sqrt( 5)
Subtract 2 from each side
p+2-2 = -2 ±sqrt( 5)
p = -2 ±sqrt( 5)